1989
DOI: 10.1177/002224378902600110
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of Marketing Professionals about Ethical Issues in Marketing Research: A Replication and Extension

Abstract: The authors examine, in the context of Crawford's 1970 study, changes in marketing professionals’ research ethics judgments and the influence of organizational factors on those judgments. The results indicate several significant changes in ethical judgments. In addition, they suggest that three organizational factors—extent of ethical problems within the organization, top management actions on ethics, and organizational role (researchers vs. executives)—underlie differences in ethical judgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Murphy et al, 1992;Weeks and Nantel, 1992), while numerous other studies (10/22) have found that there is no significant relationship between the two variables (e.g. Ford et al, 1982;Hunt et al, 1984;Chonko and Hunt, 1985;Akaah and Riordan, 1989;Callan, 1992;Allen and Davis 1993;Badaracco and Webb, 1995;Brief et al, 1996;Clark and Leonard, 1998;Farrell et al, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…Murphy et al, 1992;Weeks and Nantel, 1992), while numerous other studies (10/22) have found that there is no significant relationship between the two variables (e.g. Ford et al, 1982;Hunt et al, 1984;Chonko and Hunt, 1985;Akaah and Riordan, 1989;Callan, 1992;Allen and Davis 1993;Badaracco and Webb, 1995;Brief et al, 1996;Clark and Leonard, 1998;Farrell et al, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…The overall findings have been inconclusive. For example, in a study of marketing professionals that used scenarios to measure a person's ethical score, females had higher scores for three of 11 scenarios (Akaah and Riordan, 1989). When ethical differences in the sales profession were studied, Dawson (1997) concluded that females were more likely to agree that behaviors described in 20 scenarios were unethical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research suggests that the ethical behavior of a corporation's leaders, including whether actions are taken against unethical behavior, has an impact on the ethical behavior of other corporate agents (Akaah and Riordan, 1989;Baumhart, 1961;Brenner and Molander, 1977;Posner and Schmidt, 1987;Soutor et al, 1994). Potential harm to the company increases if corporate agents view their directors as acting unethically and then become more likely to act illegally or unethically.…”
Section: Acting In the Best Interests Of The Corporationmentioning
confidence: 99%